Energy and information transfer in biological systems : how physics could enrich biological understanding : proceedings of the international workshop, Acireale, Catania, Italy, 18-22 September 2002 - Brizhik, Larissa S.; Ho, Mae-Wan; Musumeci, Francesco, 1949- (World Scientific, 2003)
This volume contains papers based on the workshop "Energy and Information Transfer in Biological Systems: How Physics Could Enrich Biological Understanding", held in Italy in 2002. The meeting was a forum aimed at evaluating the potential and outlooks of a modern physics approach to understanding and describing biological processes, especially regarding the transition from the microscopic chemical scenario to the macroscopic functional configurations of living matter. In this frame some leading researchers presented and discussed several basic topics, such as the photon interaction with biological systems also from the viewpoint of photon information processes and of possible applications; the influence of electromagnetic fields on the self-organization of biosystems including the nonlinear mechanism for energy transfer and storage; and the influence of the structure of water on the properties of biological matter